Towards establishing a technology transfer office at the Department of Science and Technology - Bicomong, Francisca B. (University of the Philippines Diliman, 2014)
The establishment of the DOST Technology Transfer Office (DOST-TTO) is in accordance to Article IX Sec. 20 of RA No. 10055 otherwise known as the Philippine Technology Transfer Act of 2009 which calls for the establishment of TLOs in whatever form and to adopt their own policies on IPR management and technology transfer. A TLO is an organization within a university or government body that identifies research initiatives that have the greatest commercial potential, and facilitates their commercialization. They provide strategies for these discoveries and help to guide the process to fully exploit its opportunity. Reviews of existing policies at DOST, conduct of interviews, and study of international and local best practices in establishing and administering a TTO were done. Findings show that DOST has available commercializable technologies for commercialization that warrant the establishment of a TTO. However, this endeavor requires strong commitment from the DOST management. A proposed structure for the DOST-TTO has been recommended. Also immediate course of action is summed up to include the following : a) issuance of the DOST IP Policy; b) decision on where to lodge the DOST-TTO (e.g. Central Office, TAPI or TRC); c) identification of a "dedicated" team to work on the establishment of said office through the issuance of a Special Order; d) recruitment of personnel, if necessary; e) crafting and institutionalizing of technology transfer process similar to that of Stanford's OTL; f) addressing gaps that hamper the technology transfer process; and g) setting up of the DOST revolving fund.